The Devil's Advocate approach: an interview technique for assessing consistency among deceptive and truth-telling pairs of suspects - Deeb, Haneen (Legal and criminological psychology, 2018)
Purpose. The aim of this study was to assess statement consistency in pairs of deceptive and truth-telling suspects when the Devil's Advocate approach is implemented. This approach involves asking suspects an ‘opinion-eliciting’ question for arguments that support their opinions followed by a ‘devil's advocate’ question to elicit opposing arguments. On the basis of the confirmation bias and impression management literatures, we predicted that truth-telling pairs would provide more consistent arguments in response to the opinion-eliciting question than to the devil's advocate question. Deceptive pairs were expected to be equally consistent with each other in response to both questions. Method. Forty-nine pairs of participants were matched, based on their strong opinions about a controversial topic, and were asked to either tell the truth or lie about their opinions to an interviewer. Pair members were permitted to prepare for the interview together. Each participant was interviewed individually with the devil's advocate approach. Results. Prepared truth-telling pairs were more consistent with each other in response to the opinion-eliciting question than to the devil's advocate question. However, and as predicted, deceptive pairs were equally consistent with each other in response to both questions. Conclusions. The Devil's Advocate approach seems to be a promising interview technique for assessing consistency among pairs who hold false opinions and pairs who hold true opinions. It also has implications for the consistency heuristic as consistency is not diagnostic of deception or honesty unless the interview technique is taken into consideration.